2017
DOI: 10.1063/1.5001892
|View full text |Cite
|
Sign up to set email alerts
|

Electron kinetics in capacitively coupled plasmas modulated by electron injection

Abstract: The controlling effect of an electron injection on the electron energy distribution function (EEDF) and on the energetic electron flux, in a capacitive radio-frequency argon plasma, is studied using a one-dimensional particle-in-cell/Monte Carlo collisions model. The input power of the electron beam is as small as several tens of Watts with laboratory achievable emission currents and energies. With the electron injection, the electron temperature decreases but with a significant high energy tail. The electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Therefore, kinetic method, that is, the particle‐in‐cell/Monte‐Carlo‐collision (PIC/MCC) method, can cast some new lights in this problem. Previously, we have studied the kinetic impact of a thermal electron injection, from a rf powered electrode, in a rf argon discharge, where high density and high energetic (5 eV) electron flux is generated, as both the electron density and temperature increase. This energetic electron flux provides high energy delivering to the electrode, relevant for plasma‐surface chemistry, but is not preferred in plasma processing.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, kinetic method, that is, the particle‐in‐cell/Monte‐Carlo‐collision (PIC/MCC) method, can cast some new lights in this problem. Previously, we have studied the kinetic impact of a thermal electron injection, from a rf powered electrode, in a rf argon discharge, where high density and high energetic (5 eV) electron flux is generated, as both the electron density and temperature increase. This energetic electron flux provides high energy delivering to the electrode, relevant for plasma‐surface chemistry, but is not preferred in plasma processing.…”
Section: Introductionmentioning
confidence: 99%
“…Modulation schemes to control the characteristic parameters of CCP mainly include dual-frequency (DF) or multi-frequency CCP [1,[5][6][7][8][9][10][11][12][13], hybrid CCP [14][15][16][17][18], external magnetic fields [19,20], electron beam (EB) injection CCP [21][22][23][24][25][26][27][28][29], and ion beam injection [30]. Recently, EB-driven approaches have gained considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…The hollow cathode discharge can only occur when the ion secondary emission coefficient is greater than 0.1. And the EB can improve ionization, increase plasma density, reduce ion energy, and modulate the energy distribution of electrons [19][20][21][22]. By numerical simulation, Haas et al found that electron temperature and energy distribution can be suppressed due to the high energy tail provided by the EB [19].…”
Section: Introductionmentioning
confidence: 99%
“…By numerical simulation, Haas et al found that electron temperature and energy distribution can be suppressed due to the high energy tail provided by the EB [19]. And the effects of the electron beam injected into CCP from the powered electrode and grounded electrode on modulation of the energy distribution were investigated, respectively, using a 1D PIC/MC simulation, by Zhang et al [20,21]. It was reported that compared with conventional CCPs, electron density skyrockets when the EB is injected, and the population of energetic electrons increases, too.…”
Section: Introductionmentioning
confidence: 99%